Nanotechnology-Based Drug Delivery to Improve the Therapeutic Benefits of NRF2 Modulators in Cancer Therapy - Zerrin Sezgin-Bayindir; Sonia Losada-Barreiro; Carlos Bravo-Díaz; Matej Sova; Julijana Kristl; Luciano Saso (MDPI AG, 2021)
The disadvantages of conventional anticancer drugs, such as their low bioavailability, poor targeting efficacy, and serious side effects, have led to the discovery of new therapeutic agents and potential drug delivery systems. In particular, the introduction of nano-sized drug delivery systems (NDDSs) has opened new horizons for effective cancer treatment. These are considered potential systems that provide deep tissue penetration and specific drug targeting. On the other hand, nuclear factor erythroid 2-related factor 2 (NRF2)-based anticancer treatment approaches have attracted tremendous attention and produced encouraging results. However, the lack of effective formulation strategies is one of the factors that hinder the clinical application of NRF2 modulators. In this review, we initially focus on the critical role of NRF2 in cancer cells and NRF2-based anticancer treatment. Subsequently, we review the preparation and characterization of NDDSs encapsulating NRF2 modulators and discuss their potential for cancer therapy.